Static and dynamic modelling of the South African real sector - Barr, Graham Douglas Irving (Department of Statistical Sciences, 2016)
This thesis provides a detailed investigation of the applicability of various economic models to the South African real sector. It has been written primarily for the statistician, and thus presentation of economic theory has been in a straightforward and, if possible, mathematical form. Chapter One provides an introduction to the application of econometric methods to economic model building. Chapters Two, Three and Four consider the theory and application of various economic models to the South African case. Chapter Five considers the relevance of money to the real sector.